2012
DOI: 10.3201/eid1804.111310
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin–producingEscherichia coliSerotype O78:Hin Family, Finland, 2009

Abstract: STEC carrying stx 1c and hlyA genes can invade the human bloodstream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
(27 reference statements)
2
26
1
Order By: Relevance
“…This was in agreement with many previous studies that reported the genetic relatedness between APEC and human ExPEC isolates with an explanation of the origin similarity of both isolates along with the possession of common virulence and antimicrobial resistance genes [22][23][24][25]. Meanwhile, some other studies previously isolated O78 serotypes from stools of diarrheic patients [26][27][28]. Interestingly, the presence of the same serotypes in this study (O26:H11 and O119:H4) isolated from diseased chicken viscera and human stool increases the awareness about the presence of substantial overlap at the level of serogroups between chicken and human isolates.…”
Section: Discussionsupporting
confidence: 81%
“…This was in agreement with many previous studies that reported the genetic relatedness between APEC and human ExPEC isolates with an explanation of the origin similarity of both isolates along with the possession of common virulence and antimicrobial resistance genes [22][23][24][25]. Meanwhile, some other studies previously isolated O78 serotypes from stools of diarrheic patients [26][27][28]. Interestingly, the presence of the same serotypes in this study (O26:H11 and O119:H4) isolated from diseased chicken viscera and human stool increases the awareness about the presence of substantial overlap at the level of serogroups between chicken and human isolates.…”
Section: Discussionsupporting
confidence: 81%
“…Reports of bacteremia or sepsis in patients with hemolyticuremic syndrome (HUS) caused by STEC do exist (2,(9)(10)(11). In our study, we found that almost 5% of the strains found in adult patients with bacteremia caused by E. coli carried stx 2 subtypes associated with HUS (12)(13)(14).…”
mentioning
confidence: 48%
“…aEPEC strain UR3457 belongs to phylogroup B2 (ST2018) and serotype O78:H-. Although this serotype is not frequently found in humans, it has also been reported in an STEC isolate recovered from a patient suffering from neonatal bacteremia, bloody diarrhea, and hemolytic-uremic syndrome (HUS) (62). The interconversion between some STEC and aEPEC isolates may arise via the loss and gain of Shiga toxin-coding phages (63,64).…”
Section: Discussionmentioning
confidence: 99%